(3OjhGf Uaj GdOjf GdMdjs - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s; (3GdGejhWj , EHQGgje Hf eMeO Hf YHO GdQMje Hf EHQGgje, LeGd GdOjf,J (B790 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Yde GdEfSGf GdHjGf(B: (3hef Ydjg bGd jaJNQ Ydg hbheg aj EMOi GdhbGFY(B: (3dFf KdeJ MOj UQha GdfhGFH abO CNdUJ SHcj HfGQ GdJLGQH s
(3BNQgG (B:s
(3deG QaYJ fGQce ddSGQj CfSJ Ydi GdfGQ gOi GdCSQGQ eP LFJce CQhe efgG bHSkG fhOjJ HCf HhQc ef aj GdfGQ Je GdOjhGf hced HYhf Gddg JYGdi s
(3fSNI KGfjIs
(3hQO CjVkG JMJ Qbe (B2202(3, (B2203 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B98s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B146 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B797s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs